Teaching students how to write clearly through mediation: task design for tertiary EFL writing - Oki, Emma (Neofilolog, 2026)
Drawing on the CEFR’s conceptualization of mediation (CoE, 2020) and the reader-oriented principles of clarity discussed by Williams and Bizup (2014), this article proposes a task design framework for teaching students how to write clearly in tertiary-level EFL writing instruction. It argues that clarity-focused writing tasks in which the target reader and the communicative situation are not made explicit may not fully support the development of clear writing. In such tasks, students may fail to see clarity as context-dependent, and the associated principles of clarity may appear abstract or weakly connected to the communicative demands of writing. Mediation tasks address this by including the target reader and the communicative gap in the task itself. Instead of asking students to “write clearly” for an imagined audience, they require students to decide what to select, how to formulate it, and how to organize it so that the target reader can (re)construct the intended meaning. In this way, clarity emerges as a product of mediation, since students must resolve a communicative gap through constrained decisions about selection and expression. The article shows how selected CEFR mediation activities (CoE, 2020) can be mapped onto clarity principles (Williams & Bizup, 2014), specifying how different task types may structure different writing decisions. It concludes with illustrative tasks for tertiary-level C1 students, demonstrating how the framework can be operationalized in classroom practice.